(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Aravind Adiga’s Man Booker Prize-winning debut novel The White Tiger is a high-pitched and captivating novel that actually attacks poverty and inequality without being sentimental. That is the reason why this novel is a ground breaking novel in India. This novel is written totally from the outlook of a servant. In order to explain the current Indian conditions in which poor people attempt to meet both ends, the narrator uses the word ‘the darkness’.In the novel, the narrator expressed the lives of poor people of India in a realistic and understanding manner. Adiga’s The White Tiger is the best fictional writing which actually went outside the organized onset of the natives and endeavored to exemplify the diverse and most violent impact of the majestic rule in modern India. In this paper, it is attempted to analyse the view of Adiga’s point about the present scenario of the poor people of India. The White Tiger is a story which depicted about the quest of a man for the freedom.Balram is the main character of this novel and he is the victim of poverty and injustice. Balram being the victim worked his way out of his low caste and overcame all the problems of the society which had reduced his family in the past and accomplished his objective by murdering his master, stealing his money, and becoming a successful entrepreneur. This is how the hurting and truthful picture of modern India is depicted in Adiga’s novel.